Solve the equation. -6 -21 = 3p - 12 A. 1 B. 3 C. 3 D. 1
-6 -21 = 3p - 12 ; -27 + 12 = 3p ; -15 = 3p ; p = -15/3 = -5
Question
Updated 1/19/2018 9:21:05 AM
Edited by jeifunk [1/19/2018 9:21:05 AM]
Rating
3
-6 -21 = 3p - 12 ;

-27 + 12 = 3p ;

-15 = 3p ;

p = -15/3 = -5

Confirmed by jeifunk [1/19/2018 9:21:20 AM]

29,720,152
*
Get answers from Weegy and a team of really smart live experts.
S
L
R
R
Points 1536 [Total 3051] Ratings 7 Comments 206 Invitations 126 Offline
S
L
P
C
P
C
P
C
Points 1026 [Total 4822] Ratings 5 Comments 976 Invitations 0 Offline
S
L
Points 1009 [Total 1009] Ratings 5 Comments 949 Invitations 1 Online
S
L
R
Points 915 [Total 1552] Ratings 6 Comments 315 Invitations 54 Offline
S
L
Points 618 [Total 1058] Ratings 3 Comments 568 Invitations 2 Offline
S
L
Points 480 [Total 2597] Ratings 4 Comments 440 Invitations 0 Offline
S
L
1
P
1
Points 317 [Total 1766] Ratings 9 Comments 227 Invitations 0 Offline
S
L
Points 165 [Total 658] Ratings 4 Comments 105 Invitations 2 Offline
S
L
Points 141 [Total 592] Ratings 1 Comments 131 Invitations 0 Online
S
L
Points 134 [Total 144] Ratings 0 Comments 134 Invitations 0 Offline
* Excludes moderators and previous
winners (Include)
Home | Contact | Blog | About | Terms | Privacy | © Purple Inc.